ERK activation causes epilepsy by stimulating NMDA receptor activity - Nateri, Abdolrahman S (Nature Publishing Group, 2007)
The ERK MAPK signalling pathway is a highly conserved kinase cascade linking transmembrane receptors to downstream effector mechanisms. To investigate the function of ERK in neurons, a constitutively active form of MEK1 (caMEK1) was conditionally expressed in the murine brain, which resulted in ERK activation and caused spontaneous epileptic seizures. ERK activation stimulated phosphorylation of eukaryotic translation initiation factor 4E (eIF4E) and augmented NMDA receptor 2B (NR2B) protein levels. Pharmacological inhibition of NR2B function impaired synaptic facilitation in area cornus ammonicus region 3 (CA3) in acute hippocampal slices derived from caMEK1-expressing mice and abrogated epilepsy in vivo. In addition, expression of caMEK1 caused phosphorylation of the transcription factor, cAMP response element-binding protein (CREB) and increased transcription of ephrinB2. EphrinB2 overexpression resulted in increased NR2B tyrosine phosphorylation, which was essential for caMEK1-induced epilepsy in vivo, since conditional inactivation of ephrinB2 greatly reduced seizure frequency in caMEK1 transgenic mice. Therefore, our study identifies a mechanism of epileptogenesis that links MAP kinase to Eph/Ephrin and NMDA receptor signalling.